Micro-tension and micro-shear experiments to characterize stress-state dependent ductile fracture. (1st June 2017) - Gorji, Maysam B.; Mohr, Dirk
Abstract: In view of characterizing the local plasticity and fracture properties in structures with material property gradients at the millimeter scale, a micro-tension and micro-shear testing technique is developed. It makes use of flat dogbone-shaped, notched, central hole and smiley-shear micro-specimens that have been scaled down from their macroscopic counterparts in a way that the critical gage section dimensions do not exceed 500 μm. A new tensile loading device is designed to apply the loading at speed of less than 1 μm/s to achieve strain rate of about 10 −3 /s at the gage section level. The device includes custom-made clamps without any floating parts that guarantee the alignment of the specimen with respect to the loading axis as well as the uniformity of the applied displacement fields. In-situ experiments on aluminum alloy 6016-T4 are carried out in an optical microscope. Planar digital image correlation is used to compute the surface strain fields. The parameters of the Swift-Voce hardening law and the Hosford-Coulomb fracture initiation model are identified based on the micro-experiments. The obtained material data is validated through numerical simulations of macroscopic fracture experiments that have been performed on the same material. Graphical abstract: Image 1